Build the life you want ebook The art and science of getting happier. - Brooks, Arthur C. (2023)
You can get happier. And getting there will be the adventure of your lifetime. INSTANT #1 NEW YORK TIMES BESTSELLER In Build the Life You Want , Arthur C. Brooks and Oprah Winfrey invite you to begin a journey toward greater happiness no matter how challenging your circumstances. Drawing on cutting-edge science and their years of helping people translate ideas into action, they show you how to improve your life right now instead of waiting for the outside world to change. With insight, compassion, and hope, Brooks and Winfrey reveal how the tools of emotional self-management can change your life―immediately. They recommend practical, research-based practices to build the four pillars of happiness: family, friendship, work, and faith. And along the way, they share hard-earned wisdom from their own lives and careers as well as the witness of regular people whose lives are joyful despite setbacks and hardship. Equipped with the tools of emotional self-management and ready to build your four pillars, you can take control of your present and future rather than hoping and waiting for your circumstances to improve. Build the Life You Want is your blueprint for a better life.